Neuroendocrine Mechanisms Underlying Non-breeding Aggression: Common Strategies Between Birds and Fish - Quintana, Laura; Jalabert, Cecilia; Fokidis, H. Bobby; Soma, Kiran K.; Zubizarreta, Lucia (Frontiers in Neural Circuits, 2021)
Aggression is an adaptive behavior that plays an important role in gaining access to limited resources. Aggression may occur uncoupled from reproduction, thus offering a valuable context to further understand its neural and hormonal regulation. This review focuses on the contributions from song sparrows (Melospiza melodia) and the weakly electric banded knifefish (Gymnotus omarorum). Together, these models offer clues about the underlying mechanisms of non-breeding aggression, especially the potential roles of neuropeptide Y (NPY) and brain-derived estrogens. The orexigenic NPY is well-conserved between birds and teleost fish, increases in response to low food intake, and influences sex steroid synthesis. In non-breeding M. melodia, NPY increases in the social behavior network, and NPY-Y1 receptor expression is upregulated in response to a territorial challenge. In G. omarorum, NPY is upregulated in the preoptic area of dominant, but not subordinate, individuals. We hypothesize that NPY may signal a seasonal decrease in food availability and promote non-breeding aggression. In both animal models, non-breeding aggression is estrogen-dependent but gonad-independent. In non-breeding M. melodia, neurosteroid synthesis rapidly increases in response to a territorial challenge. In G. omarorum, brain aromatase is upregulated in dominant but not subordinate fish. In both species, the dramatic decrease in food availability in the non-breeding season may promote non-breeding aggression, via changes in NPY and/or neurosteroid signaling.